The Importance of Context Marker Element in Developing Bandung Techno Park as A Tourist Attraction - Adrian Agoes; Ersy Ervina (Journal of Business on Hospitality and Tourism, 2015)
Increasing visitors to Bandung Techno Park (BTP) indicates the potential resources it has to develop as a visitor or tourist attraction. In spite of that, the management of this facility sees it largely as a form of impediment that slows down the pace of their business. They mainly consider the Techno Park to its primary function; becoming the hub connecting the ICT society consists of Business, Academic, and Government. In fact Bandung Techno Park is also meant to become the centre of scientific transmission to educate the people around it, particularly in regards to ICT. It shows that the increasing visit of the general community actually is in line with the BTP’s vision, transmitting the knowledge about ICT to the people. Nonetheless, the case in BTP is that the management has difficulties in handling the visitors who increasingly outnumber the available staffs with no particular skill and facilities needed in handling visitors. This study has observed the facilities and interviewed the management of BTP to find out some of the feature needed in developing tourist attraction. The article focuses on one element, which is Context Marker, to establish the Techno Park to be a suitable tourist attraction for future visitors.